2024
DOI: 10.3390/nu16071054
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Psychobiotics in Depression: A Modern Approach through the Microbiota–Gut–Brain Axis: A Literature Review

Angela Dziedzic,
Karina Maciak,
Katarzyna Bliźniewska-Kowalska
et al.

Abstract: The microbiota–gut–brain (MGB) axis is a complex communication network linking the gut, microbiota, and brain, influencing various aspects of health and disease. Dysbiosis, a disturbance in the gut microbiome equilibrium, can significantly impact the MGB axis, leading to alterations in microbial composition and function. Emerging evidence highlights the connection between microbiota alterations and neurological and psychiatric disorders, including depression. This review explores the potential of psychobiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 196 publications
(230 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have observed two-way communication between the microbiota and the brain ( Kunugi, 2021 ; Sharma et al, 2021 ; Trzeciak and Herbet, 2021 ; Ye et al, 2021 ; Hou et al, 2022 ; Dziedzic et al, 2024 ) through the gut–brain axis, which encompasses multiple components, including the CNS, spinal cord, autonomic nervous system, enteric nervous system, immune system, and hypothalamic–pituitary–adrenal axis ( Carabotti et al, 2015 ). The gut microbiota can produce various molecules that act at distal sites to imitate the function of endocrine organs ( Tsigos et al, 2000 ; Clarke et al, 2014 ), such as short-chain fatty acids (SCFAs), neurotransmitters (including serotonin, dopamine, norepinephrine, and γ-aminobutyric acid), cholic acids, tryptophan, L-dopa, adipokines, and hormones ( Clarke et al, 2014 ).…”
Section: The Gut–brain Axismentioning
confidence: 99%
“…Numerous studies have observed two-way communication between the microbiota and the brain ( Kunugi, 2021 ; Sharma et al, 2021 ; Trzeciak and Herbet, 2021 ; Ye et al, 2021 ; Hou et al, 2022 ; Dziedzic et al, 2024 ) through the gut–brain axis, which encompasses multiple components, including the CNS, spinal cord, autonomic nervous system, enteric nervous system, immune system, and hypothalamic–pituitary–adrenal axis ( Carabotti et al, 2015 ). The gut microbiota can produce various molecules that act at distal sites to imitate the function of endocrine organs ( Tsigos et al, 2000 ; Clarke et al, 2014 ), such as short-chain fatty acids (SCFAs), neurotransmitters (including serotonin, dopamine, norepinephrine, and γ-aminobutyric acid), cholic acids, tryptophan, L-dopa, adipokines, and hormones ( Clarke et al, 2014 ).…”
Section: The Gut–brain Axismentioning
confidence: 99%